Modulação autonômica cardíaca e níveis séricos de sulfato de dehidroepiandrosterona em idosos fisicamente ativos praticantes de treinamento físico concorrente - MELO, Poliana Morais (2014)
The age-related decline in dehydroepiandrosterone sulfate (DHEA-S) production is currently attracting attention because of its possible relevance to the etiology and management of age-related clinical disorders. Several abnormalities of cardiovascular system function have been described in the elderly. Among them, cardiac autonomic dysfunction has been reported. Data obtained recently by our group shows, for the first time, that serum DHEA-S decreased are associated with lower heart rate variability (HRV) in sedentary elderly. Thus, the aim of this study was to investigate in elderly physically active practitioners of concurrent exercise training the serum DHEA-S concentrations and its association with HRV. Twenty-two elderly of both sexes with 66.1 ± 4.9 years-old participated of this study and were separated in two groups: active (n=12) and sedentary (n=10). We evaluated anthropometric characteristics and body composition, as well as heart rate (HR), blood pressure (BP), rate pressure product (RPP), time (TD) and frequency (FD) domain parameters of HRV in resting and during the active postural maneuver, the serum DHEA-S and cortisol concentrations. For all statistical analysis we used the significance p<0.05. We did not find differences in the anthropometric characteristics and body composition between both elderly groups. On the other hand, the active elderly group showed a higher resting bradycardia when compared to the sedentary elderly group. No differences in baseline parameters of BP and RPP were found between groups. The HRV results in FD analysis demonstrated that the sedentary elderly showed a higher sympathetic modulation and a lower parasympathetic modulation in resting in comparison to active elderly. After the orthostatic test, however, we noted a lesser response of HR and RPP as well as sympathetic modulation measured by mean of spectral analysis in sedentary group in relation to active group. The DHEA-S hormone is reduced in sedentary elderly. On the other hand, the serum concentration of cortisol was not different between groups of this study. Our analyses showed no significant correlation between DHEA-S and variance of HRV. The data support the concept that the increase of DHEA-S in elderly physically active is not related to cardiac autonomic modulation. In addition, our results suggested that sedentary elderly had a marked autonomic dysfunction and a lower hormonal production which may constitute an important mechanism linking aging to cardiovascular risk.